PENGARUH APLIKASI TIKTOK TERHADAP KESANTUNAN BERBAHASA PADA SISWA KELAS ATAS SDN CIPELANG GEDE - Mutmainah, Siti; Barkah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of TikTok app usage on the politeness of upper-grade elementary school students. The study employed a quantitative approach with an explanatory design using an ex post facto method. The study population was all 66 fourth and fifth-grade students at Cipelang Gede Elementary School. The sampling technique used total sampling, ensuring that the entire population served as respondents. Data collection was conducted using a Likert-scale questionnaire measuring two main variables: TikTok usage and politeness. Data analysis was conducted through descriptive statistics, prerequisite analysis tests, including normality and linearity tests, and hypothesis testing using Pearson correlation and simple linear regression using SPSS version 16 software. The results showed that students' levels of TikTok usage and politeness were moderate. However, the regression test showed that TikTok use had no significant effect on students' politeness (R = 0.113; R² = 0.013; p = 0.367). These findings suggest that social media exposure does not directly determine students' communication behavior. Other factors such as character education, school culture, and parental supervision likely play a more dominant role in shaping students' politeness.